Cultural identity and origins of humanity in Felipe Guamán Poma de Ayala - Cuculiza, María Nelly (1987)
The work that we propose here has been carried out taking as an object of analysis a set of stories present in the "Nueva Crónica y Buen Gobierno" by Felipe Guamán Poma de Ayala (Guamán poma, 1980). As its name indicates, it is a chronicle that was written in Peru between the end of the 16th century and the beginning of the 17th century. The last wording is presumed for around 1610-1615 (Adorno, 1980), that is, before a century had passed since the Spanish conquest. Very little is known about the author, Guamán Poma, apart from what he presents about himself, his family and his environment in the chronicle itself. It was apparently an Indian of relative nobility, although it is difficult to discern because the time is characterized by a barrage of probanzas, documents that the Indian nobles, as well as the not so noble, addressed to the Spanish authorities in order to prove their ancestry. and thus preserve certain privileges (Murra, 1980).